Clinical, Paraclinical Characteristics and Pathogens of Pneumonia in Children at the Pediatric Deparment, Bach Mai Hospital - Van Dem, Phsm; Thanh Nam, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 2DO - 10.25073/2588-1132/vnumps.4236, 2020)
This study describes the clinical, paraclinical characteristics and pathogens of pneumonia in 195 children with pneumonia at the Pediatric Department, Bach Mai Hospital from January to June 2019. According to the study results, most of the cases were aged under five (93.3%) with pneumonia clinical features of tachypnea, 99%; cough, 97.4%; crackling sound, 81.6%; respiratory failure, 80.5%; leukocytosis, 55.9%; and high CRP level in serum, 54.9%. There were 90 cases positive with incubated bacteria with the prevalence of three nasopharyngeal carriages: S.pneumoniae was 48.7%; H.influenzae, 27.8%; and M.catarrhalis, 18.3%. All the bacteria were susceptible to almost all the antibiotics used in treatment, such as Amoxicillin/acid clavunamic, cefotaxim and ceftriason. The study concludes that c linical and paraclinical characteristics in children with pneumonia were fairly various and bacterial pathogens of pediatric pneumonia were similar and susceptible to basic antibiotics. Keywords Pneumonia, Steptococcus pneumoniae, Haemophilus influenzae, antibiotic-resistant. References [1] T.K.P. Nguyen, T.H.Tran, C.L. Roberts et al, Child pneumonia – focus on the Western Pacific Region, Paediatr Respir Rev 21 (2017) 102-110. [2] P.M.M. Yan Jin, Jose Irineu, Rigotti et al, Cause-specific child mortality performance and contributions to all-cause child mortality, and number of child lives saved during the Millennium Development Goals era: a country-level analysis, Glob Health Action 11(1) (2018) 1-20. [3] L. Liu, S. Oza, D. Hogan et al, Global, regional, and national causes of under-5 mortality in 2000–15: an updated systematic analysis with implications for the Sustainable Development Goals, Lancet Child Adolesc Health 16 (2016) 31593-31598. [4] WHO, World Health Statistics, 2015. [5] Bonita F. Stanton and Richard E. Behrman (2016), Overview of Pediatrics, Robert M. Kliegman Nelson Text Book of Pediatrics, 20th Edition, (Elsevier), Philadelphia, 20-39. [6] L.N. Tra, Biologycal constant of Vietnamese in 90th decade, 20th century. Medical Publishing house, Hanoi ( 2004). [7] WHO, Anemia. Global Database on Anaemia, (2015) 4-9. [8] Thomas Bénet, Sánchez Picot, Mélina Messaoudi et al, Microorganisms Associated With Pneumonia in Children <5 Years of Age in Developing and Emerging Countries: The GABRIEL Pneumonia Multicenter, Prospective, Case-Control Study, Clin Infect Dis 65(4) (2018) 604–612. [9] S.E. Katz and D.J. Williams, Pediatric Community-Acquired Pneumonia in the United States Changing Epidemiology, Diagnostic and Therapeutic Challenges, and Areas for Future, Infect Dis Clin North Am 32(1) (2018) 47–63. [10] Yi-Yi Yu, Luo Ren, Yu Deng et al, Epidemiological characteristics of nasopharyngeal Streptococcus pneumoniae strains among children with pneumonia in Chongqing, China, Sci Rep (9) (2019) 1-8. [11] Mohamed M Rashad, Sahar M Fayed and Aly Mona K El-Hag, Iron-deficiency anemia as a risk factor for pneumonia in children, Benha Medical Journal 32(2) (2015) 96-100. [12] Sopio Chochua, Valérie D'Acremont, Christiane Hanke et al, Increased Nasopharyngeal Density and Concurrent Carriage of Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis Are Associated with Pneumonia in Febrile Children, PLoS One 11(12) (2016) 1-12. [13] Le Thi Hong Hanh, Đao Minh Tuan, Nguyen Duy Bo et al, Pneumonia at the Respiratory Department and Allergy Immunology Department of National Children Hospital in 2015, Vietnam Medical Journal 447 (2016) 70-75. [14] Ministry of Health, Guinline diagnosis and treatment pneumonia in children, 2015. [15] A. Zafar, R. Hasan, S. Nizamuddin,, Antibiotic susceptibility in Streptococcus pneumoniae, Haemophilus influenzae and Streptococcus pyogenes in Pakistan: a review of results from the Survey of Antibiotic Resistance (SOAR) 2002–15, J Antimicrob Chemother 71(1) (2016) 103-109.